Faktor-Faktor yang Mempengaruhi Kinerja Guru di Sekolah Dasar - Arief Al- Syauqi; Maulidana Hidayatullah Harahap; Cut Kumala Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Elementary school teacher performance plays a pivotal role in enhancing the learning process. This study investigates key elements that affect teacher performance, including personal (internal) aspects, environmental (external) influences, leadership from school principals, and levels of teacher professionalism. Using a literature review approach, the study compiles data from relevant sources. The results reveal that teacher performance is shaped by motivation, satisfaction at work, support from school management, and both pedagogical and professional competence. This suggests that improving teacher effectiveness requires a holistic strategy. The study implies the importance of formulating education policies that continuously support teacher development and strengthen leadership to foster a productive educational climate.